2018
DOI: 10.1007/s11748-018-1020-0
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative intervention by oral medicine team in cardiovascular surgery patients

Abstract: In brief, perioperative oral intervention consists of elimination of odontogenic foci and maintenance of oral hygiene in patients undergoing surgery. The importance of oral intervention before, during, and after medical treatments is well known, especially in cancer patients, because odontogenic foci such as untreated deep dental caries or periodontitis can cause systemic infection in patients with myelosuppression resulting from chemotherapy. Although perioperative oral intervention is currently recommended f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
(60 reference statements)
0
11
0
2
Order By: Relevance
“…40 In recent years, preoperative oral intervention has received considerable attention for its effectiveness in preventing nosocomial pneumonia in cardiovascular surgery patients. 10,40,41 Suzuki et al revealed that preoperative periodontal treatment can reduce the risk of postoperative infection. 42 On the other hand, a recent systematic review demonstrated that it is unclear whether dental treatment before cardiovascular surgery prevents postoperative complications or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In recent years, preoperative oral intervention has received considerable attention for its effectiveness in preventing nosocomial pneumonia in cardiovascular surgery patients. 10,40,41 Suzuki et al revealed that preoperative periodontal treatment can reduce the risk of postoperative infection. 42 On the other hand, a recent systematic review demonstrated that it is unclear whether dental treatment before cardiovascular surgery prevents postoperative complications or not.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Perioperative oral intervention and optimal strategies for such intervention are recommended; however, the effect of oral health status on postoperative outcomes in cardiovascular surgery patients is rarely considered. 10 Importantly, postoperative functional recovery or activity of daily living (ADL) is of crucial importance because inadequate functional recovery or ADL at discharge predicts adverse cardiac events over the next year. 11,12 Therefore, we investigated the relationship between preoperative oral health status and functional recovery or postoperative outcomes after cardiovascular surgery.…”
Section: R Esum Ementioning
confidence: 99%
“…It has been reported that oral care prevents pneumonia. (Akashi, Nanba, Kusumoto, & Komori, ; Mizuno et al, ; Yoneyama, Yoshida, Matsui, & Sasaki, ) Conversely, some treatment guidelines do not require oral care. (Lassen et al, ; Mangram, Horan, Pearson, Silver, & Jarvis, ) This discrepancy is considered to be due to the fact that there are no high‐level evidence studies on the effects of POM.…”
Section: Discussionmentioning
confidence: 99%
“…O acompanhamento odontológico no pré-operatório de cirurgias cardiovasculares é fundamental para remoção de focos infecciosos, melhorando a condição clínica do paciente. (AKASHI et al, 2018). Não existe um protocolo padrão para triagem odontológica que relacione o controle de infecções e o período adequado para realização dos procedimentos antes da cirurgia cardiovascular (COTTI et al, 2019).…”
Section: Introductionunclassified
“…Quando o período pré-operatório é curto,Akashi et al (2018) contraindicam a realização de procedimentos invasivos, como exodontias e raspagem, para evitar hemorragias inesperadas e o adiamento da cirurgia cardiovascular. Contudo, em casos de dentes com drenagem purulenta persistente ou com periodontite avançada e risco de avulsão durante a intubação, os autores indicam a exodontia, mesmo um dia antes da cirurgia cardiovascular, e ressaltam que durante o pós-operatório os pacientes oral profissional de rotina e os demais procedimentos poderão ser realizados quando houver estabilidade no quadro clínico.…”
unclassified